Strengthening Food Safety Governance in Nepal through Collaborative Capacity Development and Private Sector Engagement - Joshi, Prateek; Karn, Sanjeev Kumar; Koirala, Pramod (Journal of Agriculture and Environment, 2023)
This article discusses the policy and regulatory challenges faced by Nepal in strengthening food safety governance and the potential solutions to address them. Capacity building through training programs and technical assistance, regional collaboration, and private sector engagement are the key strategies identified for improving food safety standards in the country. The article highlights the need for a comprehensive legal framework and the establishment of a centralized food safety authority in Nepal. The challenges faced by the private sector in complying with food safety standards are also discussed, particularly the difficulties faced by small and medium-sized enterprises. The potential benefits of regional collaboration in the food sector, including the harmonization of food standards, the development of regional frameworks for food safety based on the Codex, and the creation of a regional food safety rapid alert system, are also examined. The article concludes that addressing policy and regulatory challenges through capacity building, regional collaboration, and private sector engagement can lead to improved food safety governance in Nepal and help the country to overcome its food safety challenges.